Analisa Tingkat Kepuasan Pengguna Kereta Api Kota Padang - Doni Setiawan (Universitas Putra Indonesia YPTK Padang, 2020)
The problem that often occurs in cities is structuring the city, starting with settlements, spatial planning, poor communities and transportation, as well as the city of Padang. The increasing number of people needing transportation, especially the destination of Padang-Minangkabau International Airport, is one of the reasons for the opening of the train station. Because the train has several advantages compared to other land transportation equipment, which are relatively cheap costs, can sit freely, faster,and safer. The purpose of this study was to determine how much public interest in railroad modes of transportation by analyzing the level of satisfaction of train users in accordance with the response from the public.The Coefficient of Determination (R2) is obtained from the Adjusted R Square number of 0.404. This shows that the contribution of variables of comfort, safety, safety, time, transportation rates, and service to the users of the Padang-Minangkabau International Airport train are 0.404 or 40.4% while the remaining 59.6% is influenced by other variables not examined in this study. From this result, get a value of 40.4% which indicates that the services provided by PT. Kereta Api Indonesia has not been good and users have not been satisfied with the performance of the Padang-Minangkabau International Airport train service